Strength and Durability of Cement Sand Brick Containing Palm Oil Fuel ash (POFA) and Fine Recycled Concrete as Partial Cement Replacement - ISMAIL, SAKINAH; SHEIKH KHALID, FAISAL (Recent Trends in Civil Engineering and Built Environment, 2022)
Nowadays, the growths of the construction industry are increasing directly proportional to the human population to fulfil their living needs. The consumption of construction and industrial wastes have grown rapidly across the world which leads to creating large quantities of wastes. It was reflected to the problem of having a limited number of landfills due to a huge amount of waste produced. One of the alternative is recycle the waste and make a good product. Following a through literature review, recycled aggregates are aggregates derived from the processing of materials previously used in a product or in construction industry and palm oil fuel ash (POFA) is a by-product in palm oil mill. Therefore, this study promoted utilization of recycled concrete aggregate (RCA) and POFA as suitable materials to be partial cement replacement materials in the construction industry. The construction cost reduces by using industrial wastes and helps to protect the natural environment from the disposal of wastes. The main objective of this study is to determine the sand cement brick properties containing POFA, fine recycled concrete wastes, such as compressive, and water absorption tests. The mix design for the modified sand cement brick is 5%, 10% and 15% of RCA and POFA. Water cement ratio that would be used in this research is 0.6. Testing for compressive strength would be measure at 7 and 28 days and for water absorption only at 28 days.  This research finds that with combination of 10% and 5% of POFA with 31.8 MPa for compressive strength and 5.4% for water absorption was the optimum mix design to replace cement in sand cement brick. This research helps to improve the knowledge, increase the level of environmental awareness and understanding the importance and recycling the construction waste generated.